Phenotypic Distribution of Human Morphogenetic Traits and Abo-Rh Blood Groups - Kamil S Mohamed (Journal of Scientific and Human Dimensions, 2026)
Human morphogenetic traits are hereditary physical characteristics that are inherited as autosomal dominant or recessive traits and show differential expressions among various populations. These traits have been used as classical examples in human genetics for many decades and continue to remain an important area of study in population genetics, medical genetics, and forensic science. The current literature related to the phenotypic expression of nine major morphogenetic traits, such as tongue rolling, earlobe attachment, widow’s peak, cleft chin, dimpled cheeks, hitchhiker’s thumb, bent little finger, mid-phalangeal hair, and polydactyly, in relation to ABO-Rh blood group systems, is synthesized in this review article, particularly focusing on studies conducted in Nigeria, Lesotho, Pakistan, China, and other parts of the world, to understand the sex differences, geographical variability, and genetic complexities related to these traits. The findings suggest that many morphogenetic traits, which were earlier considered to be simple hereditary traits, might have a complex mode of inheritance, and studies related to ABO blood group systems might provide an exciting area for research, although it has been largely neglected in the past. The methodological limitations, such as bio-cultural context and population stratification, have also been highlighted for future research.